2018
DOI: 10.1037/emo0000383
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of state and trait mindfulness on the late positive potential.

Abstract: Mindfulness is an effective emotion regulation strategy, and its principles have formed the basis for several psychotherapies. Of interest is how a mindful perspective changes not only the subjective experience of emotion, but also neural activity involved in emotional processing. In a previous event-related potential (ERP) study, trait mindfulness was linked with reduced neural activity in response to affective stimuli, as measured by the late positive potential (LPP). Building on this result, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 79 publications
0
16
0
1
Order By: Relevance
“…However, the effect was not observed in the case of a task-induced state of mindfulness, where participants were instructed to pay attention to emotional stimuli with a mindful mindset. In this case, an increase in emotional response (Egan et al, 2018;Uusberg et al, 2016) or a lack of change has been reported (Lin et al, 2016). These mixed findings suggest that outcomes could be a function of the experimental context.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, the effect was not observed in the case of a task-induced state of mindfulness, where participants were instructed to pay attention to emotional stimuli with a mindful mindset. In this case, an increase in emotional response (Egan et al, 2018;Uusberg et al, 2016) or a lack of change has been reported (Lin et al, 2016). These mixed findings suggest that outcomes could be a function of the experimental context.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, mindfulness was associated with higher LPP amplitude in two studies (Egan, Hill, & Foti, 2018;Uusberg, Uusberg, Talpsep, & Paaver, 2016), and three studies reported no effect (Cosme & Wiens, 2015;Ho, Sun, Ting, Chan, & Lee, 2015;Lin et al, 2016). It should be noted that two studies found a mixed effect of mindfulness on the LPP component, depending on the experimental condition (dispositional mindfulness, meditative state or MM intervention) (Egan et al, 2018;Lin et al, 2016).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, findings by Sobolewski, Holt, Kublik, and Wróbel [89] have found meditators to experience lower LPP in response to negative valence stimuli, but were no different from controls in response to positive valence stimuli, suggesting that meditators were better able to regulate negatively arousing emotions. On the other hand, Egan, Hill, and Foti [82] found increased LPP regardless of affective valence and arousal. Egan et al [82] attributed this finding to the nature of their study, such that the brief mindfulness instruction in their study requested participants to focus their attention to external stimuli (pictures on the screen), which would have in turn led to increased LPP to reflect emotional processing of the stimuli to which focus was directed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Egan, Hill, and Foti [82] found increased LPP regardless of affective valence and arousal. Egan et al [82] attributed this finding to the nature of their study, such that the brief mindfulness instruction in their study requested participants to focus their attention to external stimuli (pictures on the screen), which would have in turn led to increased LPP to reflect emotional processing of the stimuli to which focus was directed. As such, the ERP findings thus far allude to the role of mindfulness meditation in the motivated allocation of attention resources, which could have important implications for how attention is allocated toward feared stimuli in the context of fear extinction.…”
Section: Introductionmentioning
confidence: 99%